Citric Acid Sweet Potato Extraction Beverages Containing Grape Juice and Fermented Glutinous Rice Syrup - Teangpook, C.; Panthavee, W.; Puminat, W.; Thalang, V.N. (Pakistan Journal of Nutrition, 2012)
Beverages were developed from three cultivars of sweet potato, with orange-purple-and yellow-colored flesh that were mixed with grape juice and with two cultivars of fermented rice beverage (white and black glutinous rice). The beverage with the optimum formula consisted of 44.98% purple-colored flesh of sweet potato juice extraction (extracted with 0.5% citric acid solution), 40% red grape juice, 6% white fermented glutinous rice syrup, 9% sucrose and 0.02% sodium chloride. The product was a pinkish-purple color and cloudy. The total soluble solids, pH, L*, a*, b*,% titratable acidity (as citric acid) and anthocyanin were 16.95°Brix, 3.60, 4.82, 9.08, 6.56, 0.42% and 4.82 unit/g, respectively. The average score from sensory evaluation produced a moderate result. The product was placed in glass bottles at 80-90°C, tightly closed and then steamed with gas stove for 5 min. After storage for 3 month at room temperature, the sensory test of overall liking of the products decreased to little liked. The product was found to be microbiologically safe, but the color and total anthocyanins content had decreased. The product was found to have no measurable anticancer properties on human breast adenocarcinoma, lung carcinoma and epidermoid carcinoma of the oral cavity and had a noncytotoxic effect on the Vero cell line.